Two new species of the genus Cryptotendipes Lenz (Diptera: Chironomidae) from India with a worldwide key to the genus. (2nd January 2019) - Pal, Gargi; Hazra, Niladri
Abstract: Adult males of Cryptotendipes aculeatus sp. nov. and Cryptotendipes disparilis sp. nov. are described and illustrated from India. This is the first record of the genus Cryptotendipes Lenz from India. A key to the worldwide species of adult males of Cryptotendipes is also provided. http://zoobank.org/urn:lsid:zoobank.org:pub:B9835E8E-6F1E-4EC2-A114-6D1260CCF9DF